CROWN SEPARATION WITH USE ELECTROFULGURATION AT BOTTOM OF DENTAL CAVITY - S.V. Irkha (Ukrainian Medical Stomatological Academy, 2015)
Actuality of theme. In recent years the development of endodontics and the use of new technologies enhanced the efficiency of root canal treatment. But this does not completely solve the problem of the teeth roots perforation in the area of furcation. Surgical removal of pathological process of perforation method of furcation of teeth roots is necessary way to preserve the tooth and eliminate chronic inflammation of the surrounding tissue. There is a number of methods offered by specialists to treat this complication, but these methods not always achieve positive results and serve as reasons: the inability to create proper sealants, due to low mechanical strength of the material, the lack of reliable adhesion to tooth tissues; state surrounding periodontal tissues at the site of perforation. One of the promising materials that is used to close the perforation of the bottom cavity of the tooth and root canals is MTA Pro Root (mineral trioxide aggregate), Dentsply, USA. The method is based on the usage of special cement, consisting of powder (small hydrophilic particles of calcium oxide and silica) and liquid (in an amount necessary for optimum mixing powder). Powder also contains small amounts of oxides of other minerals that are responsible for chemical and physical quality of the material, including bismuth oxide powder. MTA has high pH, because this material has a pronounced bactericidal potential. When mixing cement forms mass of gel slowly solidifies. MTA is biocompatible material with paradontium and is perceived as an inert substance similar to bone. Sealing ability of MTA, according to the authors, is not changed while contacting with blood. Coming into contact with the periapical tissues, MTA causes formation of fibrous connective tissue and cement. To increase the effectiveness of dental treatment of destroyed furcation is applied the developed by us method of crown separation using electrosurgical method - electrofulhuration. Materials and methods. We have decided to treat 15 patients aged 21 to 40 years old. People applied to the clinic complaining of pain in their teeth, mostly pain in lower permanent molars after endodontic treatment at dental therapists. All patients were examined radiographically. Dental radiography was performed before treatment and during the long term (up to 2 years). Conclusion. Application of our proposed method of crown separation with usage of elektrofulguration perforation of bottom tooth cavity allows you to create access to the site of inflammation (the affected area) and hold sparing the destruction of abnormal tissue, as well as provide a reliable antiseptic wound surface and root canals prior to obturation by intratubular ozonation for further prosthetics. The proposed method allows you to save damaged teeth roots and to use them as additional denture supports in order to reduce the functional load on the abutments of the patient and thus improve the quality of compensation defect of the tooth crown in the destruction of the bifurcation.